A novel noninvasive index for nonalcoholic steatohepatitis: a pilot study. (November 2013) - Polyzos, Stergios A.; Kountouras, Jannis; Slavakis, Aristeidis; Zafeiriadou, Efthimia; Patsiaoura, Kalliopi; Katsiki, Evangelia; Zavos, Christos; Papatheodorou, Athanasios; Terpos, Evangelos
Abstract Objective: The potential development of a noninvasive marker predicting nonalcoholic steatohepatitis (NASH). Methods: Thirty patients with biopsy-proven nonalcoholic fatty liver disease were evaluated by numerous anthropometric, clinical and biochemical parameters. Results: Serum glutamic oxaloacetic transaminase (SGOT; p = 0.027), log (erythrocyte sedimentation rate) (ESR; p = 0.034) and homocysteine (p = 0.041) were associated with NASH independently from gender, age and body mass index. When combined, the regression model provided R2 = 0.563 (p = 0.001) and area under the ROC curve = 0.873 ± 0.066 (p < 0.001). Conclusion: This noninvasive marker, named HSENSI (acronym of homocysteine, SGOT, ESR, Nonalcoholic Steatohepatitis Index), consists of three low cost, easily measurable parameters and may accurately predict NASH.